La actividad lúdica como estrategia para el desarrollo de la inteligencia interpersonal en los niños de inicial 2 del centro de educación inicial (caritas alegres) de la parroquia Augusto N. Martínez, del cantón Ambato, provincia de Tungurahua, período académico 2014 - 2015 - Pérez López, Ligia Mercedes (2016)
This research began by stating the problem which is expressed in the question- How does a recreational activity influence the development of interpersonal intelligence in children of Caritas Alegres Early Education Center in Augusto N. Martinez district, belonging to Ambato Country, in the province of Tungurahua during to academic period of 2014 – 2015? Afterwards, both overall objectives and specific ones were set. This also included the identification of the games which teachers use to subsequently interrelate them with the development of social intelligence. Taking into consideration the need and importance of the issue by involving children that require greater attention in the development of abilities and skills in their social relationships. In addition, principals such as: philosophical, epistemological, psychological, pedagogical, axiological were also contemplated. The theoretical framework encompasses topics and subtopics which consist of both independent and dependent variables with their corresponding operationalization. The research methodology contains the type of methods, such as deductive and inductive with their analytical and synthetic processes, types and research design. An adequate population was used with all the necessary techniques and instruments, then, all the tabulations, analysis and interpretation of results were made which later led to the conclusions and recommendations. These recreational activities promote meaningful learning which contribute directly in improving the social intelligence necessary in society, authentic performance and more liberal educations achievements. Finally, a proposal has been prepared which contains a number of grouped activities assigned to solve the difficulties encountered. It also describes the activity, subject, object, process, materials, and evaluation with its corresponding evaluation indicator.